Pengaruh Model Contextual Teaching and Learning (CTL) dan Motivasi Berprestasi terhadap Student Engagement Mahasiswa Tata Rias - Aniesa Puspa Arum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
This study uses quantitative comparative approach with experimental method to make-up artistry student at State University of Jakarta. Contextual teaching and learn- ing (CTL)-group models for experimental classes and contextual teaching and learning (CTL)-individual models for control classes. The analysis uses ANAVA and Tukey’s test. The results: (1) the student engagement of those who use CTL-group models are higher than those who use CTL-individual models, (2), there were interactions between CTL models use and achievement motivation to the student engagement tata rias student, (3), the student engagement of those with high achievement motivation who use CTL-individual models are higher than those who use CTL-group models, and (4) the student engagement of those with low achievement motivation who use CTL-group models are higher than those who use CTL-individual models.